Enhancing Low-Frequency Microwave Absorption Through Structural Polarization Modulation of MXenes - Shan, Bo; Wang, Yang; Ji, Xinyi; Huang, Yi (Nano-Micro Letters, 2024)
Two-dimensional carbon-based materials have shown promising electromagnetic wave absorption capabilities in mid- and high-frequency ranges, but face challenges in low-frequency absorption due to limited control over polarization response mechanisms and ambiguous resonance behavior. In this study, we propose a novel approach to enhance absorption efficiency in aligned three-dimensional (3D) MXene/CNF (cellulose nanofibers) cavities by modifying polarization properties and manipulating resonance response in the 3D MXene architecture. This controlled polarization mechanism results in a significant shift of the main absorption region from the X-band to the S-band, leading to a remarkable reflection loss value of − 47.9 dB in the low-frequency range. Furthermore, our findings revealed the importance of the oriented electromagnetic coupling in influencing electromagnetic response and microwave absorption properties. The present study inspired us to develop a generic strategy for low-frequency tuned absorption in the absence of magnetic element participation, while orientation-induced polarization and the derived magnetic resonance coupling are the key controlling factors of the method. Highlights: 1 MXene-based structural microwave-absorbing materials achieve an impressive reflection loss of − 47.9 dB in the low-frequency S-band, without the presence of magnetic materials and with low density. 2 The elucidation of the mechanism behind the shift of the absorption band from high to low frequencies is attributed to the coupling of controlled multilevel polarization with induced electric field interactions.